Stereoselective Metal-Free Reaction of Imidazoles with Isothiocyanates Involving Cyanophenylacetylene: A Shortcut to N-(Z-Alkenyl)imidazole-2-carbothioamides - Trofimov, Boris A.; Andriyankova, Ludmila V.; Nikitina, Lina P.; Belyaeva, Kseniya V.; Mal’kina, Anastasiya G.; Afonin, Andrei V.; Ushakov, Igor A. (Synlett, 2012)
N-(Z)-(2-Cyano-1-phenylethenyl)imidazole-2-carbothioamides have been synthesized in up to 91% yield by the new reaction between 1-substituted imidazoles and isothiocyanates in the presence of cyanophenylacetylene under catalyst- and solvent-free conditions at room temperature. The reaction proceeds via zwitterion–carbene intermediates which are trapped by isothiocyanates to form the zwitterion with ambident N–S anionic site, which then undergoes stereo- and regioselective migration of the alkenyl moiety.
Keywords: alkynes; carbenes; multicomponent reaction; nucleophilic addition; stereoselectivity